Imaging Pediatric Plasmacytoid Dendritic Cell Neoplasm With FDG PET/CT: Atypical Presentation of a Rare Disease. (May 2016) - Martineau, Patrick; Pelletier-Galarneau, Matthieu; Turpin, Sophie; Lambert, Raymond
Abstract : Abstract: Blastic plasmacytoid dendritic cell neoplasm is a rare malignancy characterized by cutaneous involvement and hematological dissemination. Most affected patients are older, usually in the sixth or seventh decade of life, and this condition has rarely been described in the pediatric population. This report presents the case of a 9-year-old boy with blastic plasmacytoid dendritic cell neoplasm and demonstrates the utility of FDG PET/CT for staging and treatment follow-up.